KELOMPOK DUKUNGAN UNTUK CAREGIVER ORANG DENGAN SKIZOFRENIA - Menaldi, Adhityawarman; Dewi, Hellen Citra (Faculty of Psychology, Diponegoro University, 2019)
Caregiver’s burden not only affects the mental health of the caregiver, but also to the treated patient. This study aims to examine the effectivity of support group intervention to reduce caregiver burden among mothers of individuals with schizophrenia. The study used a quasi-experimental one-group, before-after (pretest-posttest) design, involving nine participants. The intervention consisted of four sessions, including pre and post-intervention session with three hours duration per session at average. Caregiver’s burden was measured using the Zarit Burden Interview (ZBI). Qualitative data on the participants’ experiences during intervention were collected using unstandardized nonstructured interview. Quantitative data were analyzed using Wilcoxon Signed Ranks Test while qualitative data were analyzed using content analysis. The result shows that the interventions proved significantly reduced caregiver’s burden scores (Z = -2.67; p = 0.008). In addition, the participants reported more positive thoughts, better control on negative emotions, positive meaning, and new hope about their future after the intervention. Participants also reported to gain new knowledge, coping strategies skills as caregiver and how to take care of their children with schizophrenia.